Computer simulation applied to structural analysis and experimental applications of natural deep eutectic solvents - Souza, Otávio Aguiar [UNESP]; Rinaldo, Daniel [UNESP]; Porto, Caio M.; Sambrano, Júlio R. [UNESP]; Morgon, Nelson H.; de Souza, Aguinaldo R. [UNESP] (Elsevier, 2021)
Modern chemistry has the objective of reducing environmental impacts and the costs of chemical processes. The search for the most viable theoretical methodologies to better understand the process itself is related to this objective. One of the major challenges for the chemical industry is the replacement or elimination of toxic conventional solvents. This chapter focuses on the roles of computational chemistry in the investigation of alternative solvents and predictions of their properties. In particular, it considers a new class of alternative solvents known as the deep eutectic solvent (DES), and their subclass of natural deep eutectic solvents (NADES), which are perceived as promising green solvents suitable to replace toxic ones. Their potential uses are wide-ranging (e.g., in the extraction of fragrances and drugs from natural sources, in the preparation of dyes, agrochemicals and cosmetics, in synthesis processes, and in enzymatically controlled reactions). Their physical properties and selectivity depend on the kind of interactions among the molecules of the eutectic mixture and/or with the target molecules. Computational studies constitute a powerful tool in the search for a better understanding of the correlation between the molecular structure and the chemical and physical properties of these materials, thus helping in the design and prevision of the stability and properties of new NADES before their experimental preparation, reducing both time and costs. After a detailed description of the history, properties, and potentialities of NADES, this chapter presents a computational study of a glucose-proline NADES, to better highlight the roles of computational research for the design of new NADES with green properties.
Keywords: Atoms-in-molecules (AIM) method; Density functional theory; Eutectic mixtures; Glucose-proline interaction energy; Glucose-proline NADES; Green extraction media; Green solvents; Intermolecular hydrogen bonds; Natural deep eutectic solvents (NADES); Non-covalent interaction (NIC) analysis